2x+3(3x-1)=41

Simple and best practice solution for 2x+3(3x-1)=41 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+3(3x-1)=41 equation:


Simplifying
2x + 3(3x + -1) = 41

Reorder the terms:
2x + 3(-1 + 3x) = 41
2x + (-1 * 3 + 3x * 3) = 41
2x + (-3 + 9x) = 41

Reorder the terms:
-3 + 2x + 9x = 41

Combine like terms: 2x + 9x = 11x
-3 + 11x = 41

Solving
-3 + 11x = 41

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 11x = 41 + 3

Combine like terms: -3 + 3 = 0
0 + 11x = 41 + 3
11x = 41 + 3

Combine like terms: 41 + 3 = 44
11x = 44

Divide each side by '11'.
x = 4

Simplifying
x = 4

See similar equations:

| 40+14y=-2-8y-6 | | 20x+10y=100 | | -41=7x-3x+7 | | 9x-5=-3x+19 | | 4(3-2x)=2(2x+6) | | 16z^2+16z+3=0 | | -7+7x-3x=-39 | | 9x^2+144=0 | | -8(y-10)-15=-2y-(y-5) | | 10y-16=5(2y+4) | | 5x-8+3x=72 | | 2y-5y+7=13 | | 2x+8y=34 | | x(x^2-3x-4)= | | .25+.14x=.17+.17x | | 3(2z-3)=5(z+3) | | 4+2x-5x=-2 | | -6y+3x=-1 | | 3b(6b^2-5b-7)= | | 4(2x+5)=6(5x-4) | | 0.75t-0.83=0.66t | | 6=x+x+6 | | 2x*25=30x | | 2(y+2)=3y-4 | | 2w+5x-11y+6w=9x+6y | | 2w+5x-11y+6w=9x-6y | | 4x+3(1+2x)=73 | | 7-2x=-5 | | 1+4x=29 | | v+8=2 | | 4t-4=16 | | 8ef+5ef-ef= |

Equations solver categories